Managing teams and groups - West, Michael (Henry Stewart Talks, 2010)
The role of teams in the work place, Factors that influence effective team work, Distinction between real and pseudo team working, The critical success factors for teams: clear objectives, clear roles, good communication and reflexivity, Team member knowledge, skills and abilities for team work, Barriers to effective team work, The importance of positive team environments to encourage effectiveness and innovation